2018
DOI: 10.1590/0366-69132018643722483
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the diameter of ground date pits on the technological properties of clay bricks

Abstract: The main aim of this study was to evaluate the effect of diameter of ground date pits (GDP) on the technological properties of a clay brick. For this purpose, increasing amounts of GDP (0, 5, 10, 15 and 20 wt%) with different diameters were mixed with a clay to produce clay bricks by pressing, drying and then firing at 900 °C. The GDP diameter and content changed the water requirement for plasticity. The shrinkage, water absorption and apparent porosity of fired clay brick increased with the content and diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
0
0
Order By: Relevance
“…The CR diffractogram revealed the presence of calcite, muscovite, quartz, kaolinite, palygorskite, clinochlore, dolomite, gypsum, and albite. This result correlated well with that of the chemical composition (Table I) [21]. The chemical analysis of MT (Table I) showed that SiO 2 and Al 2 O 3 had the highest major oxide contents, 64.34% and 15.72%, respectively.…”
Section: Physicochemical Characterization Of Raw Materialssupporting
confidence: 83%
“…The CR diffractogram revealed the presence of calcite, muscovite, quartz, kaolinite, palygorskite, clinochlore, dolomite, gypsum, and albite. This result correlated well with that of the chemical composition (Table I) [21]. The chemical analysis of MT (Table I) showed that SiO 2 and Al 2 O 3 had the highest major oxide contents, 64.34% and 15.72%, respectively.…”
Section: Physicochemical Characterization Of Raw Materialssupporting
confidence: 83%
“…These materials refer to bricks that are lighter than traditional bricks, and are primarily aimed at improving thermal insulation. In this line of research, a number of residues have already been tested, including sawdust, charcoal, paper sludge and straw [2], crushed date stone [3], olive pomace [4], rice husk ash [5], tea waste [6], cherry seeds [7], cigarette butts [8], and peanut hulls used as a partial replacement for sand in cement blocks [9]. Lamrani et al [10] have used peanut shells as an additive in plaster to improve insulation and reduce density.…”
Section: Introductionmentioning
confidence: 99%